Outdoor Play Environment in Early Childhood for Children - Undiyaundeye, Florence (European Journal of Social Science Education and Research, 2014)
Every adult is aware that children enjoy playing. Even before a child is able to grasp an object, bright coloured toys are suspended in a crib or held for him to enjoy. Once the child is able to crawl, stand and walk, the opportunity to explore the environment and play are expanded. Through rich educational programmes young children can demonstrate effective learning and significant development. This even has been developed to explore ways to create an outstanding environment for children under three years. It will examine ways to achieve consistent high standards across education programmes through creating rich, varied and imaginative experiences for children. Outdoor play environment offers the children much needed exercise, sunshine and the opportunity to practice motor skills in a different setting. Through a supportive outdoor play environment, the children are exposed to best support for children's emotional, social, physical development and ways of acquiring communicative and language skills so that they are exceptionally well equipped for school and next steps in their learning. A combination of inspiring and motivated exciting environment provides the child with the grounds for learning through play and experience and a different type of freedom and confidence in exploration of nature and habitat.
Keywords: Environment, Outdoor play, Play, Children, Learning and Development